Students’ readiness on language distance learning: Case of translation teaching - Ferry Safriandi; Roswani Siregar; Risnawaty Risnawaty; Milisi Sembiring (International Journal of Evaluation and Research in Education (IJERE), 2022)
The outbreak of COVID-19 has brought the disrupt change to education activities; from face to face to distance learning. In large-scale e-learning implementations, both teachers and students face an overload of subject material, making it difficult to adjust to the online context. This qualitative research investigated the students’ perception of e-learning implementation from the perspective of translation-course participants. The perception reflected the student challenges that categorized as adaptability to e-learning environment; technical availability and computer literacy; time-management, learning engagement; and self-effort and readiness. A semi structured-questionnaire Google Form that consisted of 19 items was developed to collect the students' perceptions and opinions. The questionnaire distributed and collected online. The data was tabulated, presented, and analyzed statistically. The perception of students on e-learning revealed the importance of improvement on technical support for learning instruction and material presentation, as well as students’ self-discipline on learning schedule. The finding of this study was feedback for authors to provide effective teaching by consideration to student's challenges in the e-learning environment.